Some multiplication properties of M2x2(F) - Gareb, Dr. Najmaddin Hama (Sulaimani Journal for Pure and Applied Sciences, 2014)
This work is divided into two parts; first we find all matrices which commutative with any given matrix, and second devoted to some multiplication commutative properties of M2x2(F), where F is a field. Moreover some cases which the ring M2x2(F) become commutative are studied.